Solve for x:
-3 (3 x + 15) - (x + 10) = 35
-3 (3 x + 15) = -9 x - 45:
-9 x - 45 - (x + 10) = 35
-(x + 10) = -x - 10:
-9 x + -x - 10 - 45 = 35
Grouping like terms, -x - 9 x - 45 - 10 = (-9 x - x) + (-45 - 10):
(-9 x - x) + (-45 - 10) = 35
-9 x - x = -10 x:
-10 x + (-45 - 10) = 35
-45 - 10 = -55:
-55 - 10 x = 35
Add 55 to both sides:
(55 - 55) - 10 x = 55 + 35
55 - 55 = 0:
-10 x = 35 + 55
35 + 55 = 90:
-10 x = 90
Divide both sides of -10 x = 90 by -10:
(-10 x)/(-10) = 90/(-10)
(-10)/(-10) = 1:
x = 90/(-10)
The gcd of 90 and -10 is 10, so 90/(-10) = (10×9)/(10 (-1)) = 10/10×9/(-1) = 9/(-1):
x = 9/(-1)
Multiply numerator and denominator of 9/(-1) by -1:
Answer: x = -9